EMPAT LAFADZ DZIKIR DAN MASJID SEBAGAI IDE PENCIPTAAN KALIGRAFI DALAM SENI KRIYA KULIT - Mr. Rubingun (SURYA SENI, 2008)
Four Lafads Inspiring Features to Create Calligraphy in LeatherCraft. Dzikir is believed to be a medium of calling and remembering Allah by articulating particular words or sentences as they were taught by Rasulullah. Dzikir is not only an effective means to bring about feelings of peacefulness and tranquillity, but also an inspiring source to create leather craft product. The underlying aspect of dzikir messages reﬂ ected in the works of art is the spiritualpower of  dzikir itself. It is expected that the messages may remind people to be always aware that they will always encounter some problems in life. The calligraphy presented as a work of art in the current project was  created through a sequence of methods consisting of the exploration stage, design process, (alternative designs and selected one), and the production stage. The messages of dzikir were represented in the form of calligraphy with some modiﬁ cation in Arabic which was subsequently applied in the form of a mosque. The calligraphy of dzikir and the mosque were created as a two-dimensional work of arts using teak wood, chrome and brass. It reﬂ ects the greatness of Allah and the warmness of Baitullah. Through this creation, dzikir and mosque are manifested as a work of arts which is intended both to stir up the feeling of love to God and to maintain the harmonious relationship with human beings and other creatures in the world.Keywords : dzikir, mosque, and calligraphy